O programa de avaliação da atenção básica na ótica dos profissionais de saúde e gestores* - Maria Aparecida Salci; Marcelle Paiano; Cremilde Aparecida Trindade Radovanovic; Lígia Carreira; Betina Hörner Schlindwein Meirelles; Denise Maria Vieira Guerreiro da Silva (Universidade Federal do Ceará, 2019)
Objective to understand the perception of health professionals and managers about the benefits of the National Program for Improving Access and Quality of Primary Care.Methods qualitative study based on the National Program for Improvement of Access and Quality of Primary Care and using evaluative research as methodological reference. Thirty-two health professionals participated in the study. Open interviews were used for data collection and the analytical steps of the Grounded Theory were used for the analysis, with the aid of ATLAS.ti software.Results the Program brought improvements to the practice of care, which before the evaluation were not valued or developed by professionals. However, shortcomings were detected, especially regarding the conduct of the evaluation process.Conclusion according to the study participants, the Program promoted positive experiences, which culminated in the reorganization of some activities. However, shortcomings were pointed out, mainly regarding the normative character of this evaluation.